178k views
0 votes
3/x+2 = 2/x−1 pleasee help

User ArielGro
by
6.8k points

1 Answer

4 votes
So you have:

(3)/(x) + 2 = (2)/(x) - 1

1) Start off by multiplying both sides by x to simplify the problem:

(3)/(x) + 2 = (2)/(x) - 1 \\ x((3)/(x) + 2) = ((2)/(x) - 1)x\\ 3 + 2x = 2 - x

2) Now isolate the x by moving all terms with x onto one side and all other terms onto the other side:

3 + 2x = 2 - x\\ 3x = -1

3) Finally, divide by 3 on both sides to find the value of x:

3x = -1\\ x = (-1)/(3)

------

Answer: x =
(-1)/(3)
User Mdarwi
by
5.8k points